MUSIK KLASIK DAN PENINGKATAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS TINGGI - Jayanti Dwiputri Abdi; Irma Rosalinda (Journal of Research and Measurement in Psychology, 2017)
The purpose of this study was to determine the effect of classical music to improved Mathematics learning outcomes in high grade IV, V, and VI in Binakheir Islamic Elementary School, period 2011-2012. The method used in this study is a quasi experimental, using design one-group pretest-posttest design. With the amount of research samples as many as 90 students. Students' scores in mathematics problems is obtained through data analysis techniques used to test the hypothesis is to test-t, with alpha = 0,05. Based on data analysis using t-test with significance t (0,000) < alpha set (0,05), then Ho is rejected and Ha accepted. This study therefore concludes which is classical music has a significant impact on improved student learning outcomes in mathematics higher grade IV, V, and VI elementary school.